Dosimetric properties of Gafchromic EBT films in monoenergetic medical ion beams - Martišíková, Mária; Jäkel, Oliver (Physics in medicine and biology, 2010)
For quality assurance measurements in radiotherapy with scanned ion beams, such as beam profile measurements and dosimetrical verification of patient plans, high spatial accuracy is required. We investigated the Gafchromic EBT film, which is the ancestor of the currently available EBT2 film, for this purpose.
Gesehen am 23.05.2023